2005
DOI: 10.1111/j.1365-2109.2005.01222.x
|View full text |Cite
|
Sign up to set email alerts
|

Completion of the Pacific bluefin tuna Thunnus orientalis (Temminck et Schlegel) life cycle

Abstract: Tuna aquaculture is currently dependent on the wild capture of juveniles for production. The development of hatchery technology for blue¢n and other tunas would be a major step forward in improving sustainability of their aquaculture. The present study overviews the technology in the life cycle completion of the Paci¢c blue¢n tuna (PBT) Thunnus orientalis (Temminck et Schlegel) under aquaculture conditions in Kinki University, and the problems to be solved for the establishment of tuna hatchery technology. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
189
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(193 citation statements)
references
References 18 publications
3
189
0
1
Order By: Relevance
“…These findings will shed light on behavioral traits of predatory fish in the open ocean. In tuna aquaculture, for example, a high mortality due to wall collisions has been problematic (39), which can be considered as an adverse consequence of adaptation to the bluish pelagic environment. The findings we present here are thus applicable for design of tuna farms: perceptible and high-contrast coloring.…”
Section: Resultsmentioning
confidence: 99%
“…These findings will shed light on behavioral traits of predatory fish in the open ocean. In tuna aquaculture, for example, a high mortality due to wall collisions has been problematic (39), which can be considered as an adverse consequence of adaptation to the bluish pelagic environment. The findings we present here are thus applicable for design of tuna farms: perceptible and high-contrast coloring.…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult to determine the feeding habits of larger tuna larvae from stomach data, but we know that feeding on other fish larvae is already possible when they are ~6 mm long (Miyashita et al 2001, Catalán et al 2007, Morote et al 2008, Llopiz et al 2010, and even earlier in other scombrids (Shoji & Tanaka 2001, Kaji et al 2002. The evidence for the switch from a zooplanktivorous to a piscivirous diet is clear from laboratory work where tuna larvae were observed to consume yolk-sac larvae of other species (Seoka et al 2007), becoming cannibalistic if they were not fed with enough live fish larvae of other species (Sawada et al 2005). However, identifiying the species of larval prey from field samples is very difficult due to digestion of prey and most field studies avoid it, resulting in more reports Comparison between observed (symbols as in Fig.…”
Section: Predation Potential Among Speciesmentioning
confidence: 95%
“…Maximum specific growth rate: Maximum potential growth rates were obtained using age-length relationships from laboratory experiments in Pacific bluefin tuna larvae Thunnus thynnus orientalis (up to (Miyashita et al 2001, Sawada et al 2005, Tanaka et al 2008. A relationship between age and dry weight was fitted to estimate the maximum potential specific growth rate of Pacific bluefin tuna larvae at each temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In Japan, the broodstock diet for PBT has been based on species of local baitfish and included 51 % mackerel (Scomber spp. ), 30 % jack mackerel (Trachurus japonicus), 10 % squids (Decapterus tabl, Todarodes pacificus) and 3 % sardines (Sardinops melanosticus) (Sawada et al, 2005). Similarly in Panama, YFT broodstock are fed on local baitfish and squids including Pacific anchoveta (Cetengraulis mysticetus), bigscale anchovy (Anchovia macrolepidota), market squid (Loligo opalescens), and Argentine shortfin squid (Illex argentinus) (Wexler et al, 2003).…”
Section: Broodstock Nutritionmentioning
confidence: 99%
“…Although there have been a number of attempts at NBT and PBT culture including both complete aquaculture and grow out/fattening programmes, there are few nutritional data pertaining to those studies (Buchanan, 1977;Vincent, 1981;Aitken, 1984;Okamoto et al, 1984;Belle, 1994;Doumenge, 1996). Wild-caught juvenile PBT were initially fed sand lance Ammodytes personatus, followed by anchovy Engraulis japonicus, sardine Sardinops melanosticus, jack mackerel Trachurus japonicus, mackerel scad Decapterus tabl, chub mackerel, spotted chub mackerel S. australasicus and Japanese common squid Todarodes pacificus (Sawada et al, 2005). Adult PBT were fed six days a week with a mixture of mackerel, jack mackerel, sardine and squid at a rate of 2 -3% of body weight.…”
Section: Whole Fishmentioning
confidence: 99%